Evaluation of the graphic art content of the media used in the HIV/AIDS campaign at Akatsi in the Volta Region - Fiebor, Ngkornyui (2011)
A thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfillment of the requirements for the award of Master of Arts Degree in Art Education